1951
DOI: 10.1039/jr9510002892
|View full text |Cite
|
Sign up to set email alerts
|

644. Homolytic aromatic substitution. Part I. The action of aryl radicals on nitrobenzene

Abstract: In an attempt to obtain more accurate quantitative information on substitution reactions effected by free radicals and atoms, an experimental investigation has been carried out on the extent of substitution at the 0-, m-,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1953
1953
2001
2001

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Hey et al, 1951). Moreover it can be concluded from Wheland's figures that in the special case of toluene a greater proportion of meta-substitution would occur in free-radical substitution than in electrophilic substitution.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Hey et al, 1951). Moreover it can be concluded from Wheland's figures that in the special case of toluene a greater proportion of meta-substitution would occur in free-radical substitution than in electrophilic substitution.…”
Section: Discussionmentioning
confidence: 93%
“…The occurrence of meta-substitution in free-radical reactions with nitrobenzene has been proved by De Tar & Scheifele (1951) and by Hey et al (1951) by analytical techniques. It would therefore be expected that some meta-substitution would occur when free radicals react with toluene.…”
Section: Discussionmentioning
confidence: 94%
“…The state of knowledge as it existed in 1951 is summarised in Table 4-2, which indicates that at that time it was accepted that the para isomer was the compound usually formed in greatest quantity in these reactions. At about that time Hey, Nechvatal and Robinson (1951) showed that the meta isomer, which had rarely been isolated, could, in fact, account for about 10% of the mixture of isomers in some reactions, and further results followed rapidly. Thus the composition of the isomer mixture has now been determined for a large number of arylation reactions, and the available data have been summarised by Dermer and Edmison (1957).…”
Section: Ratios Of Isomersmentioning
confidence: 99%
“…For substitution in nitrobenzene the influence of the attacking radical was demonstrated by Hey, Nechvatal and Robinson (1951), who showed that while reaction with /7-tolyl radicals gave rise to a mixture containing 9% of 4-methyl-3 '-nitrodiphenyl (arising from meta-substitution), this proportion was increased to about 12% when /7-bromophenyl radicals were used. These tendencies, which are in agreement with the theory of polarised radicals which has been developed, have been confirmed and extended by the recent work of Chang, , who studied the /7-nitrophenylation of chlorobenzene and bromobenzene, and the /7-chloro-and pbromophenylation of nitrobenzene.…”
Section: /~V -Cci>mentioning
confidence: 99%
“…As in many cases of activation toward electrophilic reagents, activating groups usually activate all positions, but the predominance of para and ortho substituted products may be understood from a consideration of the transition states for substitution of Ph-Y by radical R (5).…”
mentioning
confidence: 99%